Trend analysis of Japanese B encephalitis in the states of India during the years 2018 to 2021: an ecological study - Karthikeyan, S.; Suguna, A.; Pandi, S. (International Journal Of Community Medicine And Public Health, 2024)
Japanese encephalitis (JE) is the main form of viral encephalitis in Asia. Around 50,000 cases are seen worldwide; and 10,000 deaths per year are seen in children below 15 years of age. JE has been reported from 23 states (viz: national vector borne disease control programme (NVBDCP), geospatial analysis, India). The study is an ecological study that looks in to the pattern of occurrence (time trend-explorative study) of Japanese B encephalitis in the states of India during the years 2018-2021. The objective of this study is to determine the geospatial mortality pattern of JE in the states of India during the years 2018-2021 and also to state wise forecasting using seasonal, environmental and geospatial analysis (mapping) of Japanese B encephalitis case fatality rates (CFR). The secondary data analysis of the JE and AES from the table provided by the NVBDCP was used. The mortality pattern and the distribution of the JE cases were more pronounced in the year 2019. The JE cases and deaths in 2019 were the highest with a mean of 110.6; Standard deviation of 148.8 and case fatality rate was 25.07. With the help of better understanding of the time trend (ecological study), recommendations could be given to strengthen the interventions under the NVBDCP program.